Analysis of drought conditions and their effects on Lake Trasimeno (Central Italy) levels - Daniela Valigi; Juan Antonio Luque-Espinar; Lucio Di Matteo; Costanza Cambi; Eulogio Pardo-Igúzquiza; Mauro Rossi (Acque Sotterranee, 2016)
An analysis of drought conditions on the Lake Trasimeno area (Umbria, Central Italy) and of their influence on the lake levels is presented. Lake Trasimeno is one of the largest Italian lakes, and its economic and environmental importance is very high. The analysis of temperature data (1963-2014) shows that annual temperature is increasing – in accordance with what is known for Central Italy and the Mediterranean area – with a significant gradient of about 0.023°C/ year. No significant annual and seasonal rainfall trends were observed over the Lake Trasimeno catchment. The power spectrum analysis of rainfall and lake level fluctuations shows that both periodograms have high statistical confidence levels (>99%) for annual and semi-annual cycles. The annual cycles of the periodogram of lake level fluctuations show a higher statistical confidence level than semi-annual cycles. Some other cycles such as the El-Niño Southern oscillation, North Atlantic oscillation, and solar activity are highlighted, with significance levels lower than that of annual and semi-annual cycles. The standardized precipitation (SPI) and standardized reconnaissance drought indices, at different time scales, show that frequency and duration of extreme and severe droughts have increased in the last 25 years. A significant relationship between 12-month SPI and 12-month standardized lake levels fluctuations was obtained for the 1989-2014 period, indicating that SPI12 can be a useful indicator to represent drought severity for systems such as the Lake Trasimeno by considering lake level fluctuations rather than lake levels.